Pemulihan Korban Kekerasan Psikososial dan Kecelakaan Lalu Lintas: Studi PMH Indonesia-Malaysia - Kurnia Tanu Putra; Devina Chandra; Lioni Anggraini; Muhamad Bintang Guntoro; Fernando Lim; Felicia Jacinta Ivanka Anter (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2024)
This study compares the recovery systems for victims of psychosocial violence and traffic accidents from the perspective of Unlawful Acts (PMH) in Indonesia and Malaysia. Using library research, this study analyzes the legal framework, institutions, and social and psychological approaches used by both countries to support the victim recovery process. In Indonesia, the victim recovery system is still oriented towards material compensation and administrative settlements, with limited recognition of immaterial losses such as trauma and psychological disorders. In contrast, Malaysia has developed a victim-centered justice approach that positions victims as the subject of recovery, through regulations such as the Domestic Violence Act 1994 (Amendment 2017), the Road Transport Act 1987, and compensation mechanisms through the Motor Insurers’ Bureau of Malaysia (MIB) and the Victim Compensation Fund. This approach comprehensively integrates legal, social, and psychological recovery, including free counseling services through the One Stop Crisis Center (OSCC) and Talian Kasih 15999. The study's findings indicate that Malaysia has moved toward a holistic human recovery paradigm, while Indonesia still needs to strengthen its victim recovery system by addressing the psychological and social dimensions to align with the principles of restorative justice.